2023
DOI: 10.4103/ojo.ojo_2_22
|View full text |Cite
|
Sign up to set email alerts
|

Reticular corneal epithelial edema with topical netarsudil

Abstract: Rho-associated protein kinase inhibitor (ROCK) therapy for corneal endothelial dysfunction or damage other than glaucoma has been reported with few ocular side effects. We report reticular epithelial edema (REE) with netarsudil (0.02%) therapy in four cases with different clinical scenarios (three cases with corneal transplant and one case postcataract extraction). REE developed in all cases variably and cleared on cessation of netarsudil in three cases. One case was continued on netarsudil due to REE sparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…It is interesting to note that blepharitis is not a common adverse effect of netarsudil in contrast to ripasudil, and the reasons for this remain unclear. As with ripasudil, various studies reported the incidence of honeycomb corneal oedema caused by netarsudil [46,71,72]. However, this adverse effect was not found in any participant in the MERCURY-2 study [53].…”
Section: Safety Profile Of Netarsudilmentioning
confidence: 98%
“…It is interesting to note that blepharitis is not a common adverse effect of netarsudil in contrast to ripasudil, and the reasons for this remain unclear. As with ripasudil, various studies reported the incidence of honeycomb corneal oedema caused by netarsudil [46,71,72]. However, this adverse effect was not found in any participant in the MERCURY-2 study [53].…”
Section: Safety Profile Of Netarsudilmentioning
confidence: 98%